A Bott inverted model for equivariant unitary topological K-theory - Spitzweck, Markus; Østvær, Paul Arne (MATHEMATICA SCANDINAVICA, 2010)
Let A be an abelian compact Lie group. We show the Bott inverted suspension spectrum of the projective space that classifies A-equivariant line bundles is a model for A-equivariant unitary topological K-theory.